Incidental vocabulary recognition effects of subtitled, captioned and reverse subtitled audiovisual input - Jana van der Kolk; Sara Feijoo (Revista de Lingüística y Lenguas Aplicadas)
This study compares effects of brief exposure to L1 subtitled, L2 captioned, and reverse subtitled audiovisual input on three aspects of vocabulary learning: meaning, form, and pronunciation of target language words. A within-subjects design was used, in which three video clips in the different viewing modes were shown to ten L1 Spanish participants who underwent a pre-test, post-test, and delayed post-test of English terms that each occurred in just one of the videos. The tests measured recognition of meaning, form, and pronunciation through translation into the L1, dictation, and reading the target words aloud with native speaker ratings, respectively. The findings show statistically significant gains in producing the accurate written form of vocabulary in reverse subtitled and L2 captioned video clips, and mixed results for the other variables, including statistically significant gains in pronunciation of vocabulary with L1 subtitles.